PENGEMBANGAN SISTEM INFORMASI KESEHATAN (SIK) PUSKESMAS DI DINAS KESEHATAN KOTA METRO LAMPUNG - - Nursiyanto (IIB Darmajaya, 2011)
Puskesmas is the nearest place for people to check their health, on the other hand they are also have a duty to submit a report of activities that occur in health centers periodically to the health department. As one of the efforts to achieve these objectives, the need to build a system that can help the health center in the outpatient record data and generate reports. The system is built using multiuser technology that runs in a network of Local Area Network (LAN) architecture client / server applications are expected to be directly obtained information on the medical record in a relatively short time and can be has periodically. Data collection instrument using desk research, interviews, and documentation. While the software to build applications using MS. Visual Basic 6.0, MS. SQL Database server 2000 and crystal report 8.5. From the development of this system obtained a health information system with client / server architecture, so that the application can be run by multiple users at the same time.Keywords: information systems, health